Digital Literacy Competence among Teachers: Enhancing Teaching and Learning in the 21st-Century - Akhtar, Naeem (IJLTP, 2025)
Digital literacy competence of a teacher is currently becoming a prerequisite in successful teaching and learning in the rapidly evolving digitalized world. The paper involves the discussion of how the digital literacy competence of teachers could be used to enhance learning outcomes in classrooms in the 21st century by improving pedagogical practices. The research used a mixed-method design and examined the relationship between teacher digital skills, attitudes towards technologies and technological pedagogical knowledge (TPACK), institutional support, and student engagement. Structured questionnaires and semi-structured interviews were used to sample 300 teachers in the secondary and university levels. Quantitative data were analyzed with descriptive statistics, t-tests, regression, and ANOVA, qualitative data was analyzed with thematic analysis. It was determined that institutional support and continuous professional development are close predictors of the technology integration of the teachers and digitally skilled teachers encourage more learners to be motivated and cooperative particularly in cases where technology is integrated with pedagogical and content knowledge. The paper points out the necessity of setting up sustainable online learning environments within learning institutions. The study concludes that along the technical competency, the development of critical thinking, creative ability, and flexibility to changing technological environments enhance digital literacy of teachers.